1996
DOI: 10.1530/jrf.0.1070221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin-like growth factors and binding protein 1 on bovine granulosa cell division in anchorage-independent culture

Abstract: 5). An increase in the number of cells in the presence of IGF-I was also confirmed by DNA measurement (P < 0.05, n = 5) and by western immunoblotting analyses of La antigen (n = 3). IGFBP-1 significantly inhibited cell division stimulated by IGF-I (P < 0.001) and IGF-II (P < 0.001), but not that stimulated by the analogue, LR3IGF-I, which has low affinity for IGFBPs. Other factors also known to affect IGF synthesis or effectiveness (FSH, oestradiol, growth hormone) did not appear to influence division of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Our recent observations go further than the suggestion that not all granulosa cells have equipotential for mitosis; they suggest that there may be a population of stem cells in each follicle. Certainly a proportion of granulosa cells exhibit some of the properties of stem cells-mitosis is not inhibited by cell contact in vivo and mitosis is not dependent upon anchorage in vitro [30,42,43]. Thus, the fate and properties of the 24 granulosa cells in primordial follicles has still to be determined.…”
Section: Figmentioning
confidence: 99%
“…Our recent observations go further than the suggestion that not all granulosa cells have equipotential for mitosis; they suggest that there may be a population of stem cells in each follicle. Certainly a proportion of granulosa cells exhibit some of the properties of stem cells-mitosis is not inhibited by cell contact in vivo and mitosis is not dependent upon anchorage in vitro [30,42,43]. Thus, the fate and properties of the 24 granulosa cells in primordial follicles has still to be determined.…”
Section: Figmentioning
confidence: 99%
“…IGF-1 may be an important regulator of follicular granulosa cells maintaining their sensitivity to LH and FSH. IGFBP-1 is synthesised and secreted in human ovarian granulosa cells, which regulate IGF-1-mediated biological effects by modulating serum IGF-1 concentration (11). In the present study, the expression of IGFBP-1 mRNA decreased after ENO1 interference, indicating that its binding capacity to and inhibitory effect on IGF-1 decreased, thus indirectly leading to oestrogen secretion.…”
Section: Discussionmentioning
confidence: 44%
“…An in vitro study also confirmed that the inhibition of IGF1 signaling restored GH-induced stimulation of FSH-induced progesterone production, which suggested that endogenous IGF1 could be functionally involved with the effects of GH on progesterone production [140]. The biological effects of IGF1 have been further demonstrated to be mediated by IGF1 binding proteins, which are synthesized and secreted in human ovarian GCs [162]. Interestingly, increased free IGF1 has been demonstrated to decrease the synthesis of IGF2R, thereby allowing for more IGF2 to be bioavailable (free) for the induction of steroidogenesis and mitogenesis via the IGF1R [163].…”
Section: Gh/igfs Signaling Pathwaymentioning
confidence: 73%